Nature as a Magical Force in Gabriel Garcia Marquez’s Works (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This paper examines how nature functions as a magical force within the fiction of Gabriel García Márquez, arguing that natural phenomena are not merely descriptive backdrops but active, enchanted agents. Through a qualitative textual analysis of selected works (especially One Hundred Years of Solitude), the study identifies how storms, rains, flora, fauna and geological events act on characters and communities, bridging myth, memory and history. Findings show that nature in García Márquez’s world engages three principal modes: as mnemonic trigger, as mythic presence and as disruptive force against rational or linear temporality. The magical nature thus mirrors and shapes social and historical realities of Latin America. The discussion situates these findings in the framework of magical realism and environmental humanities, concluding that García Márquez’s portrayal of nature invites readers to recognize environment not as passive but as dynamically mythic.